Effect of delamination on the flexural response of [+45/−45/0]2s carbon fibre reinforced polymer laminates. (1st February 2019) - Liu, Zhe; Li, Peifeng; Srikanth, Narasimalu
Abstract: The damage arising in the manufacturing or service operation can result in the degradation in mechanical properties or even structural failure in composite laminates. This work investigated the flexural behaviour of [+45/−45/0]2s carbon fibre reinforced polymer laminates with the artificially embedded delamination (pre-delamination) at different interfaces. After static flexural experiments, the internal 3D damage including various failure modes was characterised and quantified in the X-ray microtomography. It was found that regardless of the pre-delamination, similar in-ply (fibre failure, matrix cracking and fibre/matrix debonding) and interlaminar (delamination) failure modes occur dominantly in the outer ply group of the compression zone in all the laminates. However, the pre-delamination and its location have the influence on both the distribution and size of the 3D damage, and thus on the flexural properties. The flexural strength that is reduced by pre-delamination is the most (least) sensitive to the pre-delamination embedded at the third (ninth) interface.